PENGEMBANGAN MEDIA VISUAL 3D STASIUN HERITAGE MENGGUNAKAN APLIKASI 3D SKETCH UP 2019 SEBAGAI IMPLEMENTASI BIM DI STASIUN DAOP 2 BANDUNG - Dicky Arisikam; Awan Hermawan Purwadinata; Abimanyu Noor Ravi Adzanto (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
Visual Media 3 Dimensions Sketch Up is a program that is used for modeling in a field of making 3-dimensional objects of buildings. The purpose of 3-dimensional visualization is to facilitate the five senses in interpreting images. This is because the ability to present visual forms must be supported by an environment that can provide clarity of information about the location of the object to be addressed by each individual. Heritage buildings contain many values ??of cultural elements. The building has aesthetic and cultural values ??both from the exterior and interior of the building. The historical value of Heritage buildings is able to provide massive evidence of an event in the past. All values ??contained in the Heritage building contribute value to the individual or community concerned. In the asset data of the station building DAOP 2 BANDUNG belonging to PT. KAI, Heritage buildings may not be destroyed or relocated. This is because the building has historical significance. As one of the efforts to maintain the shape and value of the Heritage building is to carry out 3-Dimensional digital visualization so that the original form of the building is already available in the data bank owned by PT. KAI (Persero). This also supports the implementation of BIM (Building Information Modeling) which is a digital representation of the physical characteristics and functional characteristics of a building.